Aortic valve stenosis: computed tomography prior to transcatheter aortic valve implantation (TAVI). How can the outcome be improved? - Hell, M.; Achenbach, Susanne; Arnold, Martin (Herz, 2015)
Computed tomography (CT) plays an important role in the preinterventional work-up of patients referred for transcatheter aortic valve implantation (TAVI). Contrast-enhanced CT allows a comprehensive examination with evaluation of both the vascular access route as well as aortic valve and aortic root geometry. Analysis of the minimum luminal vessel diameter, tortuosity and vascular calcification are important to determine the ability to perform the procedure via a transfemoral access. The size of the aortic annulus can be accurately measured by CT to aid selection of the appropriate prosthesis and the use of CT for prosthesis sizing has been associated with a decreased incidence of paravalvular leakage as compared to 2-dimensional echocardiography. In addition CT permits accurate assessment of aortic root anatomy, distance between coronary ostia and the annulus plane as well as the dimensions of the ascending aorta. Furthermore, suitable fluoroscopic projections that permit an exact orthogonal visualization of the aortic annulus plane by fluoroscopy during the procedure can be extracted from the CT data set. In summary, CT permits comprehensive imaging in TAVI candidates and optimizes procedural outcome.
EVALuna2:12072